Pilot clinical trial: Electronic Memory and Management Aid/smart home partnership increases aid use at three‐month follow‐up in individuals with mild cognitive impairment. (31st December 2021) - Schmitter‐Edgecombe, Maureen; Luna, Catherine; Brown, Katelyn; Cunningham, Reanne; Sumida, Catherine; Holder, Lawrence; Cook, Diane
Abstract: Background: Cognitive changes experienced by individuals with mild cognitive impairment (MCI) can impact everyday functioning and lower self‐confidence. The Electronic Memory and Management Aid (EMMA) is a senior‐friendly iOS tablet application designed to support everyday activities. To examine whether learning and sustained app use could be improved, we partnered EMMA with a smart home that delivered activity‐aware prompting. Method: In a pilot trial, participants with MCI were randomly assigned to learn to use EMMA with ( N = 14; M age = 74) or without ( N = 15; M age = 71) smart home prompting. Training consisted of 5‐6 (two‐hour) structured sessions delivered in a 4‐week timeframe by a clinician in the participant's home (half turned into smart homes). Real‐time data were collected on participant use of EMMA, with metrics averaged across these intervals: weeks 1‐2 (early‐training), 5‐6 (post‐training), 10‐11 (prompting turned off) and 15‐16 (follow‐up; prompting back on). Baseline, post‐training and follow‐up clinical data (coping, life satisfaction, everyday functioning) were also compared. Result: No group differences emerged in age, education, estimated pre‐morbid ability (High Average), memory (Low Average) or executive functioning (Average). Participants in the partnered condition engaged daily with EMMA more times post‐training ( M = 5.0) compared to the control (not‐partnered) condition ( M = 2.0). Participants in the partnered condition also maintained a high level of engagement with EMMA even after prompting stopped ( M = 5.0, M = 3.8 at follow‐up). This contrasted with significantly lowered use ( M = 1.2 and M = 0.6, respectively) in the control condition. Similar patterns were found for usage rates of app components (event scheduling, calendar use) and advanced features (searches, alarms, pictures). Clinical data showed self‐reported positive changes in coping and life satisfaction that did not differ by condition; no significant changes were self‐reported in everyday functioning. Conclusion: Partnering EMMA with a smart home that cued app use at opportune times and after periods of non‐use improved habit formation and earlier mastery of the tool. Once a habit was established, turning off the prompts did not impact use of the EMMA app, demonstrating the importance of habit formation and early mastery to sustain tool use.